Enhancing Religious Moderation Through the Management of Living Values Education at Achsaniyah Islamic Boarding School Kudus - Choir, Abu; Umi Hanik, Elya; Mubarok, Husni (At-Tarbiyat, 2025)
This study aims to explore the implementation of the Living Values Program (LVP) in enhancing religious moderation among special needs students at Achsaniyah Islamic Boarding School in Kudus. The research addresses the need for fostering tolerance, empathy, and peaceful coexistence within an inclusive educational setting. Using a qualitative field research approach, data were collected through observations, semi-structured interviews with teachers, students, and administrators, as well as document analysis. The Miles and Huberman interactive model was employed for data analysis, which includes data reduction, data display, and conclusion drawing.The findings reveal that the LVP was effectively adapted to accommodate the needs of special needs students. This research concludes that for teachers can develop universal values, namely cooperation, freedom, happiness, honesty, humility, love, peace, respect, responsibility, simplicity, tolerance, and unity so that if these values have been internalized in the teacher. The teacher will transfer and instill these values in students' habits and make living values a part of their lives. The value-based activities in the Living Values Education Program are designed to motivate students, in this case the Santri, to invite them to think about themselves, others, the world, and values in an interrelated way.